Analysing Metal Melting Methods for Green Transformation of Scrap Metal: Case Study of Latvia using MCDA and SWOT Analysis - Terjanika Viktorija; Pubule Jelena; Mihailova Elina; Zlaugotne Beate (Environmental and Climate Technologies)
Metal is one of the most widely used materials in the world. It was a crucial driving force in technological development since the industrial age and continues to push us forward to this day. As metal consumption grows, so does the amount of scrap metal generated. Proper utilization of this waste is crucial in mitigating the negative environmental impacts of the metalworking industry. The processing and use of raw materials is often associated with high resource consumption and high emissions. The utilisation of scrap metal instead of raw metal can lead to up to 10 times less electricity consumption and up to 30 times fewer CO2 emissions. However, selecting the most suitable scrap metal processing technology is crucial, particularly in the case of the metal melting furnace which is the backbone of the industry. The efficiency of this process determines the environmental indicators for the entire scrap metal melting process. This paper conducts an analysis of 8 types of metal melting furnaces based on 11 environmental criteria. Furthermore, a SWOT analysis is conducted to evaluate the efficiency of the metal smelting process in Latvian metalworking enterprises and the potential for future expansion.